Wild Floristic Diversity of Daman-Simbhanjyang Area, Makwanpur District, Central Nepal - Thapa Magar, Gyanu; Chaudhary, Sujan (International Journal of Applied Sciences and Biotechnology, 2022)
A floristic study of an area is very crucial to determine the status of plant species of particular area or geographical region, as it reflects the whole plant diversity of that area. Our study aimed at identifying the floristic composition of Daman-Simbhanjyang area which included flowering plants, gymnosperms, pteridophytes and bryophytes at wild habitat. The present study has recorded altogether 189 plant species under 163 genera and 90 families. Out of 189 plant species (114 Dicots and 20 Monocots), 134 phanerogams were recorded under 112 genera and 55 families. Asteraceae was found to be the richest family with 14 species among dicots and Orchidaceae (8 spp.) among monocots. Moreover, 30 species of pteridophytes and 22 species of bryophytes were recorded under 28 genera from 15 families and 20 genera from 17 families respectively. However, only three species of gymnosperm were recorded under 3 genera and 3 families at wild habitat. Therefore, the present study has concluded Daman-Simbhanjyang area to be rich in plant species diversity which encompasses many high valued plant species that needs to be conserved and used in sustainable manner. Int. J. Appl. Sci. Biotechnol. Vol 10(2): 112-123.